Correlation between Electronic Defect States Distribution and Device Performance of Perovskite Solar Cells. Issue 10 (6th July 2017) - Landi, Giovanni; Neitzert, Heinz Christoph; Barone, Carlo; Mauro, Costantino; Lang, Felix; Albrecht, Steve; Rech, Bernd; Pagano, Sergio
Abstract: In the present study, random current fluctuations measured at different temperatures and for different illumination levels are used to understand the charge carrier kinetics in methylammonium lead iodide CH3 NH3 PbI3 ‐based perovskite solar cells. A model, combining trapping/detrapping, recombination mechanisms, and electron–phonon scattering, is formulated evidencing how the presence of shallow and deeper band tail states influences the solar cell recombination losses. At low temperatures, the observed cascade capture process indicates that the trapping of the charge carriers by shallow defects is phonon assisted directly followed by their recombination. By increasing the temperature, a phase modification of the CH3 NH3 PbI3 absorber layer occurs and for temperatures above the phase transition at about 160 K the capture of the charge carrier takes place in two steps. The electron is first captured by a shallow defect and then it can be either emitted or thermalize down to a deeper band tail state and recombines subsequently. This result reveals that in perovskite solar cells the recombination kinetics is strongly influenced by the electron–phonon interactions. A clear correlation between the morphological structure of the perovskite grains, the energy disorder of the defect states, and the device performance is demonstrated. Abstract : A clear correlation between the morphological structure of the CH3 NH3 PbI3 grains, the energy disorder of defect states, and the device parameters in the perovskite solar cell is shown. The recombination kinetics and the charge carrier transport are strongly influenced by the electron–phonon interactions.